2011
DOI: 10.1007/s10571-011-9705-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile and Role of EphrinA1 Ligand After Spinal Cord Injury

Abstract: Spinal cord injury (SCI) triggers the re-expression of inhibitory molecules present in early stages of development, contributing to prevention of axonal regeneration. Upregulation of EphA receptor tyrosine kinases after injury suggest their involvement in the nervous system's response to damage. However, the expression profile of their ephrinA ligands after SCI is unclear. In this study, we determined the expression of ephrinA ligands after contusive SCI. Adult Sprague-Dawley female rats were injured using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 65 publications
2
12
0
Order By: Relevance
“…We found that isolated cortical neurons do indeed express the EphA2 receptor and its ligands (ephrin-A1–A3) (Fig. 5A, B, C, D, E and F), and that expressions of ephrin-A1 and ephrin-A3 was greater than that of ephrin-A2 in these cells, consistent with previous reports [5], [6], [23]. Furthermore, expression of all four proteins appeared to be increased in primary cortical neurons following 24 h of glucose deprivation (GD) in vitro (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We found that isolated cortical neurons do indeed express the EphA2 receptor and its ligands (ephrin-A1–A3) (Fig. 5A, B, C, D, E and F), and that expressions of ephrin-A1 and ephrin-A3 was greater than that of ephrin-A2 in these cells, consistent with previous reports [5], [6], [23]. Furthermore, expression of all four proteins appeared to be increased in primary cortical neurons following 24 h of glucose deprivation (GD) in vitro (Fig.…”
Section: Resultssupporting
confidence: 92%
“…These findings are particularly relevant for ischemic stroke, in which damage to cerebral endothelium and disruption of tight junctions leads to altered blood-brain barrier (BBB) permeability, contributing to post-stroke inflammation and edema. In addition, expression of both the EphA2 receptor and ephrin-A1 are known to be upregulated in various models of CNS injury [5], [6], [23]. However, it is unknown whether the EphA2 receptor plays a role in stroke-induced BBB breakdown and injury.…”
Section: Introductionmentioning
confidence: 99%
“…Here we reveal that age-dependent ephrin-A1 treatment on reactive astrocytes post-injury leads to reduced glial scar severity observed in infants following a brain injury [10], contributing to improved neuronal sparing. This is supported by prior evidence that reactive astrocyte-associated ephrin-A1 signaling contributes to functional recovery after spinal cord injury in rodents [21]. Additionally, ephrin-A1 signaling can be recapitulated following brain injury in adults to attenuate scarring and improve outcomes.…”
Section: Discussionsupporting
confidence: 58%
“…For example, ephrin-A1 and -A5 treatment elicited identical outcomes in both human and marmoset astrocytes in vitro, which differed from that observed in rodents [38]. Our conclusions highlight that ephrin-A1 signaling on reactive astrocytes [21] is required for improved functional recovery after CNS injury. Importantly the rh-ephrin-A1-fc infusion tempered rather than abrogated glial scarring in adults, providing further evidence that glial scarring is a necessary component and prerequisite to repair [12].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation